PLAN ESTRATÉGICO PARA EL TALLER DE CARROCERÍAS DE LA COOPERATIVA DE TRANSPORTES LOJA, DE LA CIUDAD DE LOJA - Reyes Girón, Janeth Elvira (2015)
As is generally known the Strategic Plan through the ages it has been to be a vital tool to meet the situational state where the shop is located opposite the internal and external environment that surrounds it. This will both raise some strategic alternatives to address the problems and threats to which they could face the aforementioned body shop, and better exploit the strengths and opportunities that arise in their daily lives. This thesis is focused on making a diagnosis and proposed implementation of a strategic plan that through this for a greater number of partners, be they of his own place or its vicinity. Thus faithfully comply with what was stated in the general target and is developing a "STRATEGIC PLAN FOR BODY WORKSHOP COOPERATIVE TRANSPORT LOJA, it will help to improve the maintenance and repair of body interprovincial vehicles are there workshop. Also it met all the specific objectives, firstly an analysis of the current situation of body shop in order to know how you are and know what their strengths and weaknesses are performed as the second specific objective was conducted an internal and external study to determine the current status of the workshop to establish what their strengths, weaknesses, opportunities and threats and third objective is to manage to integrate areas: Administrative-Financial and Human Talent, this is what achieved with their respective strategic objectives 7 It is noted that in the body shop study could identify certain shortcomings in various areas of the workshop, such as in the administrative area has no mission, vision and objectives which has led to slow growth in the local market, there inadequate planning, have no organizational or operating manuals, where it has caused duplication of functions, this being one of the major problems afflicting the workshop, as well as in the accounting area missing remodel and equip regarding furniture and equipment , office supplies and causing an unsuitable work environment, in the area of marketing has not made an ad where to publicize the services it provides, which is why the above mentioned workshop is not well known in the external environment that around to attract more partners, also in the area of service workers do not have a Personal Safety Equipment for different daily activities with regard to repair and maintenance of the units of the transport union Loja, causing hazards physical workers. Hence the importance of a strategic plan to help improve different areas of the body shop, as functional organizational structure, consistent with its current needs, and implementing new strategic policies to attract new partners to improve the positioning of the local market and economic capacity. The theoretical framework of the research was conducted, in which the planning, design objectives and everything related to the design of strategies and methodology stands which I use for better development. 8 Subsequently the results that were obtained through certain techniques and the interview with the current administrator and surveys of 23 employees and 100 partners, of which all the necessary information to meet was obtained what their strengths are detailed and weaknesses so you can define actions that one way or another will contribute to improving the current situation in which the body shop of the cooperative transport Loja is located. In the discussion of these results, where through the formulation of Situational Diagnosis Workshop respective threats, strengths, weaknesses and opportunities determined, knowing what is the situation that is happening Workshop and its shortcomings, and as is the working environment of employees. For it began with the knowledge of how they influence the political, economic, social and technological factors. In addition Competitive Profile Matrix was developed to make the respective comparison, where four companies in the sector where the following results were obtained weighted elected Workshop Cooperative Cariamanga 2.60, 2.20 Espinoza Gonzales Workshop and Workshop Brothers 2.40, indicating that the body shop of the cooperative Loja is leading with a weighting of 3.50 taking into account key factors of success. The Rating Matrix external factors and internal factors were also conducted to identify opportunities, weaknesses, strengths and threats that owns the shop, 9 also he developed an array SWOT, with their respective combinations in order to achieve strategic objectives for the workshop to improve their actions The present study proposes five strategic objectives developed detailing workable solutions to strengthen the body shop of the cooperative transport Loja in the commercial market in the city of Loja and its surroundings. In the final part of the research work a series of conclusions and recommendations were determined, which can determine a synthesis of research.